Simultaneous heptamerization of nanobody and alkaline phosphatase by self-assembly and its application for ultrasensitive immunodetection of small molecular contaminants in agro-products. (November 2022) - Xie, Guifang; Lu, Ying; Li, Wenkai; He, Zhenyun; Sun, Zhichang; Xie, Xiaoxia; Liu, Xing
Abstract: Antibody affinity and enzyme loads are two critical factors in determining the sensitivity of enzyme-linked immunosorbent assay for small molecular contaminants in food. Multimerization is considered an effective strategy to improve antibody affinity and enzyme loads. Herein, we selected ochratoxin A (OTA) as the model antigen and constructed a nanobody-alkaline phosphatase (Nb-ALP) heptamer fusion for OTA, where the Nb and ALP were simultaneously heptamerized via the self-associating peptide from the α-chains of C4 binding protein (C4bpα). The heptamer was used to develop an enhanced colorimetric enzyme immunoassay for OTA. Under the optimal experimental parameters, the proposed method has a half maximal inhibitory concentration of 0.081 ng/mL for OTA, which is 12.5-fold lower than the Nb-ALP-based method. Negligible cross-reaction was observed with OTA analogs and other common cereal mycotoxins. Moreover, good recovery rates and repeatability were obtained in the spiked cereal samples. The developed method was then applied to the analysis of OTA in real agro-products, and the results correlated well with that of the LC-MS/MS method. Overall, this work demonstrated that the simultaneous heptamerization of nanobody and alkaline phosphatase by self-assembly is an effective strategy for improving antibody affinity and enzyme loads. It also showed the great potential of Nb–C4bpα-ALP heptamer as a robust dual-functional probe for sensitive, selective, and rapid detection of mycotoxin and other small molecular contaminants in food. Graphical abstract: Image 1 Highlights: Dual-functional nanobody-alkaline phosphatase heptamer (Nb–C4bpα-ALP) for OTA. Simultaneous heptamerization of Nb and ALP by the self-assembly strategy. Nb–C4bpα-ALP shows better binding affinity and enzyme activity than Nb-ALP. Nb–C4bpα-ALP-based enzyme immunoassay for small molecules was first reported. The developed method has an IC50 of 0.081 ng/mL with the assay time of 20 min.